Stronk. - Gemeente Arnhem (Arnhem : De Vijf Zinnen, beeldentuin, 1999)
Arts, Arno ; Burgers, Henri ; Donker Duyvis, Paul ; Hemeltjen, Frank ; Hendriks, Marc ; Hendriks, Maries ; van IJzendoorn, Jan ; Kamphuis, Sicco ; Koek, Gerard ; Korvinus, Wim ; van der Laaken, Ton ; Lambertz, Ralph ; Lanters, Carel ; Lourens, Oscar ; Martinot, Nicole ; Meeuwsen, Marcel ; Meijering, Jan ; Melkert, Jeroen ; van Rooij, Mark ; van Schaaijk, Loes ; Speekenbrink, Willem ; Sweere, Rob ; Symons, Jerome ; van der Veer, Jan ; Voerman, Rob ; Vos, Jan ; Vriend, Marieke ; de Werdt, Rob van ; Wierda, Jan ; Wiersema, Marrette ; Willems, Suzanne ; Young, Lee eun ; Zwikker, Sabine
Stronk, De Vijf Zinnen, beeldentuin, Arnhem, 5 september t/m 28 november 1999
Nederlands
kunstcatalogus